POSITIVE PREDICTIVE VALUE OF NONPALPABLE BREAST LESIONS ACCORDING TO BI-RADS® CLASSIFICATION - Ney, Mônica Silva Costa Janson; Goroni, Aline Vargas; Fonseca, Giuliana Vasconcelos de Souza (Mastology, 2018)
Introduction: Breast cancer is the neoplasm that most affects women in Brazil and the world, and its incidence has increased steadily over the last decade. Due to screening mammography programs, according to age group, the mortality rate of breast cancer has decreased by 31%. With the increase in the number of screening examinations, there has also been increase in the number of suspicious lesions diagnosed and, consequently, increase in the indication and performance of breast biopsies. With the help of the categorizations that the American College of Radiology published, according to the Breast Imaging Reporting and Data System (BI-RADS®), it was possible to standardize the reports and descriptions of breast lesions, both in mammography and ultrasound, facilitating decision-making in regard to suspicious lesions. Objective: To evaluate the positive predictive value (PPV) of nonpalpable breast lesions biopsied in the Radiodiagnostic Service of Hospital Naval Marcílio Dias. Method: A retrospective and analytical study of 88 patients submitted to stereotaxic guided mammary biopsies from December 2015 to December 2016 with suspected diagnosis of malignant lesions, classified by mammographic BI-RADS in categories 4 and 5 and later correlation with the histopathological reports. Results: PPV was high for category 5 lesions, and for category 4 lesions PPV was low and progressively increased with the subcategories. Conclusion: BI‑RADS categorization is an effective predictor for the risk of malignancy in suspicious mammographic lesions.